The New Corporate StrategyThe New Corporate Strategy, by AnsoffH. Igor. New York: John Wiley and Sons, 1988, 258 pp., $24.95, cloth. - Fahey, Liam (Academy of Management Review, 1989)
The article reviews the book ?The New Corporate Strategy,? by H. Igor Ansoff.